Effect of air pollution and environmental tobacco smoke on serum hyaluronate concentrations in school children. Issue 2 (1st February 2002) - Fuji, Y; Shima, M; Ando, M; Adachi, M; Tsunetoshi, Y
Abstract : Objectives: To evaluate serum hyaluronate concentrations relative to air pollution, environmental tobacco smoke (ETS), and respiratory health in Japanese school children. Methods: Respiratory symptoms and serum IgE concentrations were examined in 1037 school children living in four communities in Japan with differing levels of air pollution. Serum hyaluronate concentrations were assayed in 230 children, consisting of all the children who had symptoms of either asthma or wheeze (65 and 50 subjects, respectively) and normal controls adjusted for sex, school grade, and school without these symptoms (115 subjects). Results: Although serum hyaluronate concentrations did not differ for either asthma or wheeze, the concentrations were significantly higher in children living in communities with higher levels of air pollution. Children with asthma or wheeze and those with serum IgE concentrations of 250 IU/ml or above showed differences in hyaluronate concentrations that related to the degree of air pollution in the communities. In children with higher serum IgE concentrations, the hyaluronate concentrations among subjects exposed to ETS were significantly higher than among those without exposure to ETS. Conclusions: The present results suggest that serum hyaluronate concentration is related to the degree of air pollution and exposure to ETS. Children with asthma or wheeze and children with higher IgE concentrations are considered to be more susceptible to environmental factors.